1989
DOI: 10.1039/f19898502381
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of preadsorbed methane with oxygen over magnesium oxide at low temperatures

Abstract: Partial oxidation by 0, of methane, which had previously been adsorbed at room temperature on MgO pretreated at 1123 K in uucuo, has been examined near room temperature by t.p.d., i.r. and e.s.r. spectroscopies and compared with a methanol adsorption system. The oxidation reaction of methane preadsorbed either in the dark or under u.v.-irradiation proceeds according to the same reaction mechanism, where low-coordination surface ions of MgO play an important role. Methane is adsorbed in a heterolytically dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The largest splitting corresponds to A xx ϭ76 G, which is in agreement with previous reports. 5,16,26 However, in the case of the sample with 63% 17 O enrichment, the ( 17 O- 16 O͒ Ϫ and ( 17 O-17 O͒ Ϫ hyperfine patterns appear simultaneously ͓see stick diagram in Fig. 2͑c͔͒.…”
Section: Omentioning
confidence: 99%
“…The largest splitting corresponds to A xx ϭ76 G, which is in agreement with previous reports. 5,16,26 However, in the case of the sample with 63% 17 O enrichment, the ( 17 O- 16 O͒ Ϫ and ( 17 O-17 O͒ Ϫ hyperfine patterns appear simultaneously ͓see stick diagram in Fig. 2͑c͔͒.…”
Section: Omentioning
confidence: 99%
“…[8] However, Ito et al reported that low coordination ions on the surface of MgO play an important role in the dissociation of adsorbed methane. [9] Defects will definitely fulfill a key function with respect to the activation of either methane or oxygen by changing the electronic structure of the wide band gap magnesium oxide particularly with regard to facilitate the transfer of electrons between the solid surface and the adsorbed molecules, which undergo a redox reaction. [10][11][12][13][14][15] The present work addresses relations between the nature and abundance of morphological surface defects such as steps and corners on pure magnesium oxide and its reactivity in the oxidative coupling of methane.…”
Section: Li-doped Mgo Was Discovered By Lunsford Et Al As An Active mentioning
confidence: 99%
“…cannot adsorb anymore, unless high reaction temperatures are applied to assure a partially dehydroxylated surface under reaction conditions. In addition, Ito et al reported that methyl radicals from the gas phase could react with surface oxygen under the formation of strongly bonded methoxide species [40] according to Eq. (2).…”
Section: Activation Of Methane On the Fresh Dehydroxylated Mgo Surfacmentioning
confidence: 99%
“…(3) [41]. Methoxide species can be transformed into carbonates at room temperature and decompose only at high temperature (T > 700 K) to produce either syngas or carbon dioxide and water [40]. Eq.…”
Section: Activation Of Methane On the Fresh Dehydroxylated Mgo Surfacmentioning
confidence: 99%